2012
DOI: 10.3748/wjg.v18.i34.4771
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of gastric intraepithelial neoplasia by narrow-band imaging and confocal laser endomicroscopy

Abstract: Higher diagnostic accuracy, sensitivity and specificity of CLE over ME-NBI indicate the feasibility of these two techniques for the efficacious diagnostic classification of gastric IN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Thirty‐six potentially relevant articles were selected for further review; among them, 23 was excluded due to the manuscript type ( n = 6), duplicates ( n = 4), animal study ( n = 1), insufficient data on diagnostic efficacy ( n = 2) or on GIN or gastric adenocarcinoma ( n = 10). Finally, 13 full‐text articles including 1 011 patients were enrolled in the meta‐analysis. The flowchart for study selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty‐six potentially relevant articles were selected for further review; among them, 23 was excluded due to the manuscript type ( n = 6), duplicates ( n = 4), animal study ( n = 1), insufficient data on diagnostic efficacy ( n = 2) or on GIN or gastric adenocarcinoma ( n = 10). Finally, 13 full‐text articles including 1 011 patients were enrolled in the meta‐analysis. The flowchart for study selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All the thirteen studies were single‐center trials, with 12 published in English and one in Chinese. Seven of the studies assessed the diagnostic efficacy of CLE for GIN, whereas nine evaluated that for gastric adenocarcinoma. Pathology was the key standard when identifying lesions in all the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The probe can be inserted through conventional endoscopes, and allows for intraoperative microscopic imaging of neoplastic and inflammatory lesions virtually throughout the entire gastrointestinal tract [8]. The clinical interest of confocal technology in the evaluation of neoplasia in Barrett's metaplasia [9], gastric [10], and colorectal [11] neoplasia seems to be increasingly confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with eCLE, pCLE is more flexible in respect of reaching sites such as the respiratory tract, liver and biliary tract. Both eCLE and pCLE have been shown to be reliable and comparable with or even superior to other modalities, such as magnifying endoscopy with or without narrow band imaing (NBI), standard endoscopy with biopsy and high‐definition white‐light endoscopy (HD‐WLE), in the diagnosis of Barrett's esophagus (BE), gastritis and gastric cancer and colorectal neoplasia.…”
Section: Introductionmentioning
confidence: 99%